Pelatihan Sablon Menggunakan Pemutih Pakaian untuk Peningkatan Kreativitas dan Ekonomi - Muhammad Farid Nasrulloh; Faisol Hidayatulloh; Zuhal Ahmadi; Sony Hidayattullah; Via Ardiana Putri (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
One of the roles of educational institutions in the context of this service is to deliver a special activity in the form of practical skills to the community. For this reason, it has been determined as the object of counseling, namely the Gabusbanaran Village Community including IPNU, IPPNU, and PKK Cadres. Screen printing using clothes bleach is an innovation from screen printing in which the coloring material relies on the color fading of a garment, which is made using materials that we use every day. Screen printing using clothes bleach also has good prospects in the convection field because there are no screen printing services in this area and there are not many service businesses using cloth bleach screen printing. The approach or method used is Service Learning (SL). From the implementation of the Screen Printing Skill activity using clothes bleach in the context of community service in Gabusbanaran Village, Tembelang District, Jombang Regency. Broadly speaking, it can be concluded that: Participants have never received knowledge and materials on screen printing using clothes bleach, Participants have high motivation, and they don't experience much difficulty in practice, the activity is very interesting and useful, Participants feel happy that they have received screen printing innovations with bleach. which they don't realize can be used to make screen printing skills.